Assessing Cerebrovascular Resistance in Patients With Sickle Cell Disease - Sayin, Ece Su; Sobczyk, Olivia; Poublanc, Julien; Mikulis, David J.; Fisher, Joseph A.; Kuo, Kevin H. M.; Duffin, James (Frontiers in Physiology, 2022)
In patients with sickle cell disease (SCD) the delivery of oxygen to the brain is compromised by anemia, abnormal rheology, and steno-occlusive vascular disease. Meeting demands for oxygen delivery requires compensatory features of brain perfusion. The cerebral vasculature’s regulatory function and reserves can be assessed by observing the flow response to a vasoactive stimulus. In a traditional approach we measured voxel-wise change in Blood Oxygen-Level Dependent (BOLD) MRI signal as a surrogate of cerebral blood flow (CBF) in response to a linear progressive ramping of end-tidal partial pressure of carbon dioxide (PETCO2). Cerebrovascular reactivity (CVR) was defined as Δ BOLD / Δ PETCO2. We used a computer model to fit a virtual sigmoid resistance curve to the progressive CBF response to the stimulus, enabling the calculation of resistance parameters: amplitude, midpoint, range response, resistance sensitivity and vasodilatory reserve. The quality of the resistance sigmoid fit was expressed as the r2 of the fit. We tested 35 patients with SCD, as well as 24 healthy subjects to provide an indication of the normal ranges of the resistance parameters. We found that gray matter CVR and resistance amplitude, range, reserve, and sensitivity is reduced in patients with SCD compared to healthy controls, while resistance midpoint was increased. This study is the first to document resistance measures in adult patients with SCD. It is also the first to score these vascular resistance measures in comparison to the normal range. We anticipate these data will complement the current understanding of the cerebral vascular pathophysiology of SCD, identify paths for therapeutic interventions, and provide biomarkers for monitoring the progress of the disease.